ANALISIS PERLAKUAN AKUNTANSI TERHADAP PRODUK CACAT DALAM PERHITUNGAN HARGA POKOK PRODUKSI PADA UD MULYO SEJATI - Tassya Rizkykha Ragilia; Linawati Linawati; Mar'atus Solikah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The background of this research is that there are defective products produced by UD Mulyo Sejati that do not meet quality standards so that they are not suitable for sale. In order not to reduce the loss of reprocessing defective products into higher quality products. The purpose of this study was to find out how the calculation, recording and treatment of defective products on the cost of production at the company UD Mulyo Sejati and to determine the effect of defective products on the cost of production at UD Mulyo Sejati. This study uses descriptive quantitative analysis techniques. The results showed that UD Mulyo Sejati kept records of production costs for 5 units of the company's products simply by recording tabulations of expenses without recording them in journal form. Whereas 1 unit of defective products accompanying the company's products is treated the same as the main product, namely the treatment is only additional production costs equal to the total costs incurred to repair the defective product of the living room table chair in the amount of idr. 300,000 defective products that were sold at UD Mulyo Sejati for idr. 3,600,000, then UD Mulyo Sejati did not experience any losses during the repairs to the defective product, even though there was an additional production cost for the defective product, it could benefit the company even if it was a small amount.